2010
DOI: 10.1007/s10029-010-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia repair in a community setting: implications for the elderly

Abstract: Inguinal herniorrhaphy under local anesthesia is a safe operation with a high success rate in the elderly. Patients with significant comorbidities are not at higher risk of complications or recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
2
8
1
2
Order By: Relevance
“…In contrast to other authors [ 10 - 13 ], major complications were 14.24% (6/42: 2 chronic inguinal pain, 4 recurrences). Minor complications were 5/42 (11.90%) and included only asymptomatic seromas that were aspirated.…”
Section: Methodscontrasting
confidence: 87%
“…In contrast to other authors [ 10 - 13 ], major complications were 14.24% (6/42: 2 chronic inguinal pain, 4 recurrences). Minor complications were 5/42 (11.90%) and included only asymptomatic seromas that were aspirated.…”
Section: Methodscontrasting
confidence: 87%
“…When elderly patients present with complications such as incarceration or strangulation, their morbidity and mortality is much higher (). As such, it would be beneficial if inguinal hernia repairs could be performed in the elderly on an elective basis (). Laparoscopic inguinal hernia repair requires general anesthesia, whereas the open technique can be carried out with local, regional, or general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent outcome studies have shown that, compared with the use of regional anesthesia, the use of general anesthesia carries with it no increase in morbidity or mortality in elderly patients (). For extremely sick patients with severe comorbidities and high operative risk, inguinal herniorrhaphy under local anesthesia should be considered (). This appropriate selection of patients and operative and anesthetic procedures could reduce the rate of severe complications that potentially lead to mortality in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that incarcerated and strangulated hernias have more serious implications in the elderly, thus supporting early elective repair in this population. However, elective repair of inguinal hernias in the elderly are more often deferred because of a perception of increased operative risk 1 …”
Section: Introductionmentioning
confidence: 99%
“…However, elective repair of inguinal hernias in the elderly are more often deferred because of a perception of increased operative risk. 1 Two methods exist for inguinal hernia repair: the open approach and the laparoscopic approach. The laparoscopic approach was introduced in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%